2004
DOI: 10.1038/sj.ijo.0802640
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to the orexigenic effect of ghrelin in dietary-induced obesity in mice: reversal upon weight loss

Abstract: BACKGROUND:Ghrelin, an endogenous ligand for growth hormone secretagogue receptor (GHS-R), is known to increase food intake in lean humans and rodents. In addition, ghrelin levels are increased by fasting in lean rodents and are elevated before meals in humans, suggesting an important role for ghrelin in meal initiation. However, in obese human, circulating ghrelin levels were found to be significantly reduced as compared to lean individuals. OBJECTIVES: To evaluate whether circulating ghrelin levels, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
78
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 39 publications
(72 reference statements)
15
78
0
2
Order By: Relevance
“…The ED 50 values when the maximal orexigenic effects were achieved at 250 min (Table 1) were in the range of mg/kg for all of the full-length analogs. The ED 50 value for subcutaneously administered ghrelin in this study was approximately 2 mg/kg, which is similar to that reported previously (Perreault et al, 2004). On the contrary, penta-and octapeptide ghrelin analogs, desoctanoyl ghr, and desoctanoyl [Dpr 3 ]ghr did not show any significant orexigenic effect even at the maximum dose of 10 mg/kg (Table 1).…”
Section: Resultssupporting
confidence: 78%
“…The ED 50 values when the maximal orexigenic effects were achieved at 250 min (Table 1) were in the range of mg/kg for all of the full-length analogs. The ED 50 value for subcutaneously administered ghrelin in this study was approximately 2 mg/kg, which is similar to that reported previously (Perreault et al, 2004). On the contrary, penta-and octapeptide ghrelin analogs, desoctanoyl ghr, and desoctanoyl [Dpr 3 ]ghr did not show any significant orexigenic effect even at the maximum dose of 10 mg/kg (Table 1).…”
Section: Resultssupporting
confidence: 78%
“…Despite the rise in total ghrelin output, n-octanoyl ghrelin levels were unaltered in Sst Ϫ/Ϫ mice. Also, fasting resulted in a rise in n-octanoyl ghrelin in both Sst ϩ/ϩ and Sst Ϫ/Ϫ mice without significant changes in total circulating ghrelin levels or stomach ghrelin gene expression, consistent with reports of others showing no effect of fasting on total circulating ghrelin levels in the mouse (29,36). This is in contrast to the effects of fasting in rats, where increases in circulating levels of noctanoyl ghrelin are clearly reflected by increases in total ghrelin levels, where ϳ90% represents the des-acyl form (31).…”
Section: Discussionsupporting
confidence: 77%
“…Another objective of the present study was to examine the effect of GLP2 on food intake in DIO mice, because the release of gut hormones is influenced by the content of the diet, in particular the fat content (Dakin et al 2004), and a different sensitivity to intestinal hormones has been reported between lean and DIO models (Lin et al 2000, Perreault et al 2004. We found that DIO mice were less sensitive to the anorectic action of the peptide than lean animals.…”
Section: Lovshinmentioning
confidence: 82%